Quality Improvement of Red Sweet Paste With using Lactobacillus plantarum - Rambe, Dita Isnaini (Universitas Bengkulu, 2024)
Red sweet potato (Ipomoea batatas L.), which contains oligosaccharides, is one of carbohydrates source in Indonesia. The oligosaccharides can benefit the growth of probiotic bacteria and increase the number of probiotic bacteria. Different heating processes can affect the physical and chemical properties of oligosaccharides contained in sweet potatoes. This study aims to assess the survival ability of L. plantarum in a suspension containing red sweet potato as a synbiotic formulation. The observed variables included the total LAB, lactic acid level, and pH values. Red sweet potato substrate with different pretreatments increased the total number of lactic acid bacteria (LAB) and lactic acid levels and decreased the synbiotic pH value. The effect of L. plantarum application on red sweet potatoes resulted atotal acid of 0.45% greater, pH reaching 3, total LAB of 11 log CFU/mL. The best result was pasta with microwave treatment because it can produce simpler sugars, has high anthocyanin levels, and has antioxidant activity.